Dampak Media Musik Dalam Pemerolehan Mufrodat Siswa Kelas Enam Tarbiyatul Athfal Bojonegoro - Muhammad A'inul Haq (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2024)
We know that in the current era there are new teaching strategies and media that can help students in the teaching and learning process. For children's level, teachers need to consider Arabic language teaching methods that suit their characteristics, such as liking playing and singing songs. Teaching Arabic and Arabic songs can be an effective tool. This research aims to develop an Arabic language education method for children and evaluate its effectiveness in improving their understanding of Arabic vocabulary through the use of songs. This research uses a quantitative approach with the type of experimental research, involving experimental and control samples consisting of 22 elementary school students. Data collection methods include observation, tests and questionnaires, with data analysis using statistical and descriptive techniques. The results of the research show that the application of the song method is effective in improving vocabulary understanding, with students repeating singing the song until they memorize it. Based on a comparison of the post-test results between the control and experimental groups, a t-statistic value of 4.635 was obtained which was greater than the t-table value of 2.228. This shows that the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted.